Targeting EGFR T790M mutation in NSCLC: From biology to evaluation and treatment. (March 2017) - Passaro, Antonio; Guerini-Rocco, Elena; Pochesci, Alessia; Vacirca, Davide; Spitaleri, Gianluca; Catania, Chiara Matilde; Rappa, Alessandra; Barberis, Massimo; de Marinis, Filippo
Graphical abstract: Abstract: The identification of EGFR mutations and their respectively tyrosine kinase inhibitors (TKIs), changed dramatically treatment and survival of patients with EGFR-positive lung cancer. Nowadays, different EGFR TKIs as afatinib, erlotinib and gefitinib are approved worldwide for the treatment of NSCLC harbouring EGFR mutations, in particular exon 19 deletions or exon 21 (Leu858Arg) substitution EGFR mutations. In first-line setting, when comparing with platinum-based chemotherapy, these target drugs improves progression-free survival, response rate and quality of life. Unfortunately, the development of different mechanism of resistance, limits the long term efficacy of these agents. The most clear mechanism of resistance is the development of EGFR Thr790Met mutation. Against this new target, different third-generation EGFR-mutant-selective TKIs, such as osimertinib, rociletinib and olmutinib, showed a great activity. In this review, we summarize the scientific evidences about biology, evaluation and treatment on NSCLC with EGFR T790M mutation.